CEA expression heterogeneity and plasticity confer resistance to the CEA-targeting bispecific immunotherapy antibody cibisatamab (CEA-TCB) in patient-derived colorectal cancer organoids. Issue 1 (15th April 2019) - Gonzalez-Exposito, Reyes; Semiannikova, Maria; Griffiths, Beatrice; Khan, Khurum; Barber, Louise J.; Woolston, Andrew; Spain, Georgia; von Loga, Katharina; Challoner, Ben; Patel, Radhika; Ranes, Michael; Swain, Amanda; et al.
Abstract : Background: The T cell bispecific antibody cibisatamab (CEA-TCB) binds Carcino-Embryonic Antigen (CEA) on cancer cells and CD3 on T cells, which triggers T cell killing of cancer cell lines expressing moderate to high levels of CEA at the cell surface. Patient derived colorectal cancer organoids (PDOs) may more accurately represent patient tumors than established cell lines which potentially enables more detailed insights into mechanisms of cibisatamab resistance and sensitivity. Methods: We established PDOs from multidrug-resistant metastatic CRCs. CEA expression of PDOs was determined by FACS and sensitivity to cibisatamab immunotherapy was assessed by co-culture of PDOs and allogeneic CD8 T cells. Results: PDOs could be categorized into 3 groups based on CEA cell-surface expression: CEAhi ( n = 3), CEAlo ( n = 1) and CEAmixed PDOs ( n = 4), that stably maintained populations of CEAhi and CEAlo cells, which has not previously been described in CRC cell lines. CEAhi PDOs were sensitive whereas CEAlo PDOs showed resistance to cibisatamab. PDOs with mixed expression showed low sensitivity to cibisatamab, suggesting that CEAlo cells maintain cancer cell growth. Culture of FACS-sorted CEAhi and CEAlo cells from PDOs with mixed CEA expression demonstrated high plasticity of CEA expression, contributing to resistance acquisition through CEA antigen loss. RNA-sequencing revealed increased WNT/β-catenin pathway activity in CEAlo cells. Cell surface CEA expression was up-regulated by inhibitors of the WNT/β-catenin pathway. Conclusions: Based on these preclinical findings, heterogeneity and plasticity of CEA expression appear to confer low cibisatamab sensitivity in PDOs, supporting further clinical evaluation of their predictive effect in CRC. Pharmacological inhibition of the WNT/β-catenin pathway may be a rational combination to sensitize CRCs to cibisatamab. Our novel PDO and T cell co-culture immunotherapy models enable pre-clinical discovery of candidate biomarkers and combination therapies that may inform and accelerate the development of immuno-oncology agents in the clinic.